A kinetics study on intercalation pseudocapacitance of layered TiS2 in K-ion batteries. Issue 47 (15th November 2019) - Zhang, Rongyu; Yang, Xu; Xu, Shifeng; Xu, Dan; Du, Fei
Abstract : The diffusion behavior of K + in layered TiS2 shows character of both capacitor and battery, which proved to be an intercalation pseudocapacitance by kinetics study. Abstract : The boundary between a capacitor and a battery is vague for layered transition metal sulfides, especially when it comes to TiS2 with a multi-phase transition process. In this work we analyzed both the quasi-static process and dynamic process of K + storage in TiS2 with carbonate based electrolytes, which proved to be an intercalation pseudocapacitive behavior.